Using Technology and the Ecological Model of Constraints to Develop Story-Based Interventions for Children with Autism Spectrum Disorder. (4th May 2018) - Mowling, Claire M.; Menear, Kristi; Dennen, Ayla; Fittipaldi-Wert, Jeanine
Abstract : The use of technology has proven to be a successful tool for enhancing the learning of children with disabilities. One example is the use of video-recorded social story movies as interventions for children with an autism spectrum disorder (ASD). Through the use of electronic devices such as iPads, iPods and tablets, social stories are brought to life in the form of a movie. Adopting a constraints approach can assist in the development of story movies. The model of constraints identifies individual, environmental and task constraints that can positively or negatively impact a child with ASD. The purpose of this article is to describe the use of technology-based story movies (social stories) as a method of delivery for story-based interventions, to provide information on how to script social stories suitable for physical education, and to explain how ecological theory and constraints can assist in the development and delivery of social stories.